Bariatric Arterial Embolization: Current Status - Khalil, Adham; Weiss, Clifford R.; Gunn, Andrew J. (Digestive Disease Interventions, 2022)
Obesity is a well-known major public health concern that causes significant morbidity and mortality with severe effects on the healthcare system and its financial status. Classic treatment options for obesity include lifestyle interventions, pharmacotherapy, and bariatric surgery. However, there is a treatment gap for patients in whom lifestyle modifications were not sufficient or satisfactory, and yet bariatric surgery is not a suitable option. Bariatric artery embolization (BAE) is a novel, minimally invasive, image-guided endovascular procedure that induces weight loss by reducing the production of appetite-mediating hormones following transarterial embolization of the gastric fundus. Recent evidence has shown that BAE is safe and effective in inducing clinically significant weight. This article will review the existing preclinical and clinical evidence on BAE, and discuss the future directions for this procedure.
Keywords: bariatric; embolization; weight loss